2015
DOI: 10.1097/rlu.0000000000000653
|View full text |Cite
|
Sign up to set email alerts
|

18F-FLT PET Imaging in a Patient With Sarcoidosis With Cardiac Involvement

Abstract: FDG PET has been proposed to play a role in the diagnosis and therapy monitoring of sarcoidosis including cardiac involvement. However, assessing inflammatory lesions in cardiac sarcoidosis using FDG can be challenging because the FDG accumulates in normal myocardium. We report a case of sarcoidosis with cardiac involvement that underwent 3'-deoxy-3'-F-fluorothymidine (FLT) PET. FLT PET images demonstrated increased uptake in the lymph nodes and left ventricle. After immunosuppressive therapy, a follow-up PET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Along with the important role of CMR and cardiac PET in the detection of ICS, radio-tracers targeting inflammatory cells such as F-18 fluorothymidine (FLT) 45 and Ga-68 DOTATOC 46 may provide additional and complementary information. Improved detection and diagnosis may facilitate a deeper understanding of the pathobiology, epidemiology, clinical characteristics, and prognosis of ICS.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the important role of CMR and cardiac PET in the detection of ICS, radio-tracers targeting inflammatory cells such as F-18 fluorothymidine (FLT) 45 and Ga-68 DOTATOC 46 may provide additional and complementary information. Improved detection and diagnosis may facilitate a deeper understanding of the pathobiology, epidemiology, clinical characteristics, and prognosis of ICS.…”
Section: Discussionmentioning
confidence: 99%
“…6; [117–119]). Though very preliminary in nature, other alternatives include hypoxia displaying agents like [ 18 F]-fluoromisonidazole (FMISO) [120] or proliferation markers like 3′-deoxy-3′-[ 18 F]-fluorothymidine (FLT) [121].
Fig.
…”
Section: Cardiac Sarcoidosismentioning
confidence: 99%
“…68 In preclinical studies, FLT uptake has been shown to be comparable to that of FDG in rat models of granulomatous disease, 69 and in recent studies FLT has been shown to accumulate in both extracardiac 70 and CS. 71,72 Additional studies are required to further evaluate the clinical utility of these novel probes for myocardial inflammation detection.…”
Section: Future Nuclear Techniques For Imaging Inflammationmentioning
confidence: 99%